Diversity of Insect Species at Different Ages of Rhizophora mucronata Stands Grown with Guludan Technique in Muara Angke, Jakarta - Siti Mayang Sari Naziah; Cecep Kusmana; Noor Farikhah Haneda (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Insects are among the most significant numbers of living things in the world that have many benefits. However, there are still many insects that have not been identified yet, for example, insects in mangrove ecosystems. Each age of the stand has differences in vegetation structure, so insect diversity research on each age difference of R. mucronata is essential. Sampling was collected by purposive sampling by taking three guludan samples measuring 5 m ´ 10 m. In each sample, a census was carried out to measure the diameter and height of R. mucronata at the age of 17, 13, 9, and 4 years for further vegetation analysis. The capture of insects is carried out using a yellow-pan trap and then identified to the level of morphospecies. The results showed a relationship between the age of different stands. At a young age had a lot of diversity and the highest value of insect abundance. The age of R. mucronata 13 years had the highest quantity dominated by the order Diptera Keywords: density, ecosystem, morphospecies, temperature, yellow-pan trap